Linkage Between Dissolved Organic Matter Transformation, Bacterial Carbon Production, and Diversity in a Shallow Oligotrophic Aquifer: Results From Flow-Through Sediment Microcosm Experiments - Hofmann, Roland; Uhl, Jenny; Hertkorn, Norbert; Griebler, Christian (Frontiers in Microbiology, 2020)
Aquifers are important reservoirs for organic carbon. A fundamental understanding of the role of groundwater ecosystems in carbon cycling, however, is still missing. Using sediment flow-through microcosms, long-term (171d) experiments were conducted to test two scenarios. First, aquifer sediment microbial communities received DOM at low concentration and typical to groundwater in terms of composition (DOM-1x). Second, sediments received an elevated concentration of DOM originating from soil (DOM-5x). Changes in DOM composition were analyzed via NMR and FT-ICR-MS. Carbon production, physiological adaptations and biodiversity of groundwater and sediment prokaryotic communities were monitored by total cell counts, substrate use arrays, and deep amplicon sequencing. The experiments showed that groundwater microbial communities do not react very fast to the sudden availability of labile organic carbon from soil in terms of carbon degradation and biomass production. It took days to weeks for incoming DOM being efficiently degraded and pronounced cell production occurred. Once conditioned, the DOM-1x supplied sediments mineralized 294(±230) µgC L-1sed d-1, 10-times less than the DOM-5x fed sediment communities (2.9(±1.1) mgC L-1sed d-1). However, the overall biomass carbon production was hardly different in the two treatments with 13.7(±4.8) µgC L-1sed d-1 and 14.3(±3.5) µgC L-1sed d-1, respectively, hinting at a significantly lower carbon use efficiency with higher DOM availability. However, the molecularly more diverse DOM from soil fostered a higher bacterial diversity. Taking the irregular inputs of labile DOM into account, shallow aquifers are assumed to have a low resilience. Lacking a highly active and responsive microbial community, oligotrophic aquifers are at high risk of contamination with organic chemicals.